2007
DOI: 10.1677/jme-07-0067
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in estrogen receptor-α protein turnover in the presence of estrogen

Abstract: Estrogen receptor-a (ERa) is essential in the maintenance of cellular responsiveness to estrogen in the reproductive system. It is established that ligand binding induces downregulation of ERa protein by targeting receptor for destruction by the 26S proteasome. However, ERa is preserved in cells chronically exposed to estrogen and it is unknown how receptor levels are maintained in the continued presence of the signal that induces degradation. A modified pulsechase analysis was developed using a tet-inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 43 publications
6
58
0
Order By: Relevance
“…ER stability has also been implicated to be regulated by posttranslational modification. For instance, phosphorylation of human ERα at Ser 118 and Ser 167 has been reported to alter ERα stability (20,21), with phosphorylated Ser 118 (pSer 118 )-ERα being resistant to proteasomal degradation (20). We examined pSer 118 -ERα levels in LTED rats and observed a robust decline in hippocampal pSER 118 -ERα levels following LTED; however, when the phospho-ERα levels were corrected with total ERα protein, there was no significant effect of LTED on pSER 118 -ERα levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ER stability has also been implicated to be regulated by posttranslational modification. For instance, phosphorylation of human ERα at Ser 118 and Ser 167 has been reported to alter ERα stability (20,21), with phosphorylated Ser 118 (pSer 118 )-ERα being resistant to proteasomal degradation (20). We examined pSer 118 -ERα levels in LTED rats and observed a robust decline in hippocampal pSER 118 -ERα levels following LTED; however, when the phospho-ERα levels were corrected with total ERα protein, there was no significant effect of LTED on pSER 118 -ERα levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). We have previously shown that synthesis of ESR1 is a major component in establishing steadystate levels of ER␣ under chronic E2 treatment (63). Physiologically, ESR1 transcript levels change in response to fluctuations in hormonal status, and a mechanism that incorporates balancing positive (p300 and AIB1) and negative (Sin3A) factors provides a plausible model to achieve such dynamic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation and quantitative real-time PCR (qRT-PCR) were carried out as previously detailed (63). The sequences of the primers used for the different gene targets are available upon request.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) Although the transcriptional mechanism of autoregulation is not fully understood, studies have shown that ligand-mediated protein degradation via 26S proteasome is involved. 6) The ubiquitin proteasome system has been implicated in cellcycle control, signal transduction, and transcription.…”
mentioning
confidence: 99%